PROSPECTS OF APPLICATION OF ORIGINAL MULTIROBOTIC SYSTEM FOR BRACHYTHERAPY OF PROSTATE CANCER - N. A. Gryaznov; G. S. Kireeva; V. V. Kharlamov; K. Yu. Senchik; D. V. Novitskiy; S. A. Nikitin (Вестник хирургии имени И.И. Грекова)
The authors analyzed the positioning error for branchytherapy needle inserted with original robotic system «Oncorobot» (Central Research Institute of Robotic And Technical Cybernetics, St. Petersburg) compared with traditional methods of insertion and other technical systems. The gelatin phantom of prostate gland was used for experiments. Needle insertion robotic program was written according to coordinates of dosimetric plan of microsourse localization. A coordinate of the needle tip location was measured after each injection of the needle into phantom and the mean-square error was calculated. It was shown that needle tip positioning error wasn’t more than 0,5 mm at insertion speeds from 3,0 to 30,00 mm/sec. Positioning error enlarged with increase of insertion speed. Needle positioning accuracy of insertion was significantly higher in case of developed robotic system, than in manual brachytherapy. The accuracy indices of the system were correlated with other described robotic systems.